Predicted digestible energy and protein intakes of steers grazing bluestem pastures - L.H. Harbers; M.R. Rao (Kansas Agricultural Experiment Station Research Reports, 1973)
Digestible protein and energy intakes by steers grazing native bluestem pastures were estimated using prediction equations established at this station. Digestible energy intakes appear to be satisfactory for yearling steers on burned and unburned pastures. Digestible protein intake is probably grater on burned than on unburned pastures; however, that nutrient becomes limiting during the grazing season.
Keywords: Cattlemen' s Day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station); 568; Beef; Protein; Energy; Steers